Analisis perbandingan kinerja keuangan perusahaan sebelum dan sesudah merger - Zalfa , Rifa Zakia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the comparison of financial performance before and after the merger. The data used are the company's quarterly financial reports for 2020 and 2021. The population in this study is the financial reports at PT. Chandra Asri Petrochemical Tbk, for the years 2020 and 2021. The sample used in this research is a saturated sample, which is a financial statement consisting of a balance sheet and profit and loss report of PT. Chandra Asri Petrochemical Tbk quarterly for the 2020 and 2021 periods. The analytical methods used are the Descriptive Statistical Test and the Wilcoxon Test. The results of the study stated that the financial performance did not experience a significant difference before and after the merger at PT. Chandra Asri Petrochemical Tbk.